Effect of Additional Amino Group to Improve the Performance of Immobilized Lipase From Aspergillus niger by Adsorption-Crosslinking Method - Nuraliyah, Andi; Perdani, Meka Saima; Putri, Dwini Normayulisa; Sahlan, Muhamad; Wijanarko, Anondho; Hermansyah, Heri (Frontiers in Energy Research, 2021)
Adsorption-crosslinking is one of the immobilization methods to improve the reusability of lipase. It requires amino groups to reduce crosslink immobilization risk so that lipase-support interaction increases and the immobilization is attainable. Also, the amino group on the support is expected to increase lipase performance. This study aimed to analyze the effect of amino group addition on immobilized Aspergillus niger lipase by the adsorption-crosslinking using MP-64 macroporous anion resin and XAD7HP macroporous non-ionic resin that has been treated with chitosan. The chitosan-coated resin was characterized by Fourier Transform Infrared Spectrometry (FTIR) and Scanning Electron Microscope (SEM). Lipase immobilization was carried out by adding 10 ml lipase solution containing 0.75 g resins and shaken at 25oC for 150 rpm. Adsorption was achieved for 4 hours, followed by crosslinking separately (adding 0.5% (v/v) glutaraldehyde and re-reacting for 20 minutes). Lipase activity was measured with the titrimetric of olive oil emulsion, mixed with Aspergillus niger lipase, emulsion, a buffer solution (pH 6.5, ionic strength of 0.7), and incubated for 30 minutes in 37oC. The effect of amino-functional groups was investigated based on lipase loading and lipase activity. The best lipase loading and lipase activity of 83.79% and 29.41 U/g support were achieved in the adsorption-crosslinking using MP-64 resin coated with chitosan. After four cycles, biodiesel synthesis was maintained at 70.61% of the initial yield. These results indicated that chitosan as an affordable and readily available source of amino groups could be used to modify support for Aspergillus niger lipase immobilization.